2023
DOI: 10.1108/ec-03-2023-0096
|View full text |Cite
|
Sign up to set email alerts
|

Unstable propagation of hydraulic fractures under varying well spacing and initiation sequence of multiple horizontal wells considering shear stress shadows

Yongliang Wang,
Nana Liu

Abstract: PurposeMulti-well hydrofracturing is an important technology to create new fractures and expand existing fractures to increase reservoir permeability. The propagation morphology of the fracture network is affected by the disturbance between the fractures initiation sequences and spacings between adjacent wells. However, it remains unclear how well spacing and initiation sequences lead to fracture propagation, deflection and connection.Design/methodology/approachIn this study, the thermal-hydro-mechanical coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Further details of this technique can be found in the references (Wang et al. , 2018; Wang and Liu, 2022, 2023; Wang et al. , 2023a, b, c).…”
Section: Geomechanical Equations Of Hydrofracturing and Microseismic ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of this technique can be found in the references (Wang et al. , 2018; Wang and Liu, 2022, 2023; Wang et al. , 2023a, b, c).…”
Section: Geomechanical Equations Of Hydrofracturing and Microseismic ...mentioning
confidence: 99%
“…Actually, some previous investigations have indicated that the above method and models can provide the effective ways to handle with the propagation of hydraulic fractures in gas reservoirs (Wang et al. , 2018; Wang and Liu, 2022, 2023; Wang et al. , 2023a, b, c).…”
Section: Numerical Models and Cases Of Multi-well Hydrofracturingmentioning
confidence: 99%
See 1 more Smart Citation